2011
DOI: 10.5009/gnl.2011.5.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Endoscopic Retrograde Cholangiopancreatography in Patients with Post-Liver Transplant Biliary Complications: Results of a Cohort Study with Long-Term Follow-Up

Abstract: Background/AimsEndoscopic retrograde cholangiopancreatography (ERCP) is the standard approach for the management of biliary complications in liver transplant patients; however, its safety and efficacy have not been established in this setting. This study was performed to evaluate the safety and long-term efficacy of ERCP in transplant patients.MethodsThe case reports of 1,500 liver transplant patients were reviewed. Orthotopic liver transplantation (OLT) patients were matched 1:2 with non-OLT patients and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 31 publications
4
39
0
Order By: Relevance
“…22 With contemporary surgical techniques, non-ABSs are relatively uncommon, occurring in less than 5% to 15% of liver transplant recipients. 20 ABSs develop from the choledochocholedochostomy or the choledochojejunostomy site and remain a common problem after transplantation; they constitute as much as 40% of biliary complications. 23 ABSs are a potential problem for all liver transplant recipients, but are particularly a problem after LDLT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 With contemporary surgical techniques, non-ABSs are relatively uncommon, occurring in less than 5% to 15% of liver transplant recipients. 20 ABSs develop from the choledochocholedochostomy or the choledochojejunostomy site and remain a common problem after transplantation; they constitute as much as 40% of biliary complications. 23 ABSs are a potential problem for all liver transplant recipients, but are particularly a problem after LDLT.…”
Section: Discussionmentioning
confidence: 99%
“…20 Posttransplantation biliary strictures are classified broadly as non-ABSs or ABSs. Non-ABSs involve donor hepatic ducts as a result of hepatic artery thrombosis 21 or ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless in some cases ERCP might not result in a definitive treatment for patients presenting with biliary concrements or strictures [14][15][16] resulting in multiple endoscopic re-interventions. Furthermore, long-term follow-up data on outcomes and complications after ERCP in liver transplant patients is scarce [17].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, patients frequently require therapeutic endoscopic retrograde cholangiography (ERCP), which can result in post-ERCP pancreatitis (PEP). A recent large systematic review of the placebo or no stent arms of PEP prophylaxis trials reported PEP rates at 9.7% and 14.7% in average-risk and high-risk patients, respectively (35)(36)(37). A number of studies in the post-liver transplant population have demonstrated lower rates of PEP varying between 1% and 6.4% (38), with 2 studies showing that PEP is responsible for 11% of post-liver transplant pancreatitis (4,7).…”
Section: Post-transplant Complicationsmentioning
confidence: 99%